Effect of intraabdominal hypertension on splanchnic blood flow in children with appendicular peritonitis - Valentyna M Perova-Sharonova; Andrew A Albokrinov; Ulbolhan A Fesenko; Taras G Gutor (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Intraabdominal hypertension (IAH) is poorly diagnosed condition that cause splanchnic hypoperfusion and abdominal organs ischemia and can lead to multiple organ failure. There are no scientific data regarding effect of intraabdominal pressure (IAP) on splanchnic circulation in children. Material and Methods: Ninety-four children after surgery for appendicular peritonitis were enrolled in the study. After IAP measurement children were included in one of two groups according IAP levels: "without IAH" (n = 51) and "with IAH" (n = 43). Superior mesenteric artery (SMA) and portal vein (PV) blood flows (BFSMA, BFPV, mL/min) were measured, and SMA and PV blood flow indexes (BFISMA, BFIPV, ml/min*m2) and abdominal perfusion pressure (APP) were calculated in both groups. Results: Median BFISMA and BFIPV in group "with IAH" were lower by 54.38% (P < 0.01) and 63.11% (P < 0.01) respectively compared to group "without IAH". There were strong significant negative correlation between IAP and BFISMA (rs = -0.66; P < 0.0001), weak significant negative correlation between IAP and BFIPV (rs = -0.36; P = 0.0001) in group "with IAH" and weak significant negative correlation between IAP and BFISMA (rs = -0.30; P = 0.0047) in group "without IAH". There were no statistically significant correlations between IAP and BFIPV in group "without IAH", between BFISMA and APP in both groups and between BFIPV and APP in both groups. Conclusion: Elevated IAP significantly reduces splanchnic blood flow in children with appendicular peritonitis. BFISMA and BFIPV negatively correlate with IAP in these patients. There is no correlation between BFISMA/BFIPV and APP in children with IAH due to appendicular peritonitis.